2021
DOI: 10.1051/aacus/2021009
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics of the banjo: measurements and sound synthesis

Abstract: Measurements of vibrational response of an American 5-string banjo and of the sounds of played notes on the instrument are presented, and contrasted with corresponding results for a steel-string guitar. A synthesis model, fine-tuned using information from the measurements, has been used to investigate what acoustical features are necessary to produce recognisable banjo-like sound, and to explore the perceptual salience of a wide range of design modifications. Recognisable banjo sound seems to depend on the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…For the simplest idealisation, treating the resonator and the rest of the banjo structure as rigid, the lowest mode of the membrane will couple to the Helmholtz resonator formed by the vented back. As shown in Figure 6 of the previous paper [1], the result is a pair of modes involving combinations of both types of motion. This behaviour is very familiar from simple models of guitar bodies [19], and also from the analysis of ducted loudspeaker enclosures (see e.g.…”
Section: Sound Radiation and Radiation Dampingmentioning
confidence: 85%
See 4 more Smart Citations
“…For the simplest idealisation, treating the resonator and the rest of the banjo structure as rigid, the lowest mode of the membrane will couple to the Helmholtz resonator formed by the vented back. As shown in Figure 6 of the previous paper [1], the result is a pair of modes involving combinations of both types of motion. This behaviour is very familiar from simple models of guitar bodies [19], and also from the analysis of ducted loudspeaker enclosures (see e.g.…”
Section: Sound Radiation and Radiation Dampingmentioning
confidence: 85%
“…In fact, it will be suggested that a "square banjo" like this would not sound very different from a normal circular one: indeed, non-circular banjo-like instruments, including rectangular ones, really exist in various corners of the world. In addition, audio demonstrations based on the model to be developed here were presented and discussed in the earlier paper [1] and the website [4]: the examples Sound B.1 and Sound B.2 on that website give a direct comparison between synthesis based on measured admittance and on the square banjo model. Later in the present paper the frequency response behaviour of the model will also be compared with that of the detailed FE/BE numerical model.…”
Section: What Makes a Membrane Different?mentioning
confidence: 99%
See 3 more Smart Citations